63 Polymorphic VT following anaphylaxis to COVID-19 vaccination. (6th October 2022) - Nic Aodha Bhuí, B; Buckley, J; Mokoka, M; MacNeill, B
Abstract : Introduction: There is little known regarding the potential cardiovascular effects, of the novel SARS-CoV-2 vaccines. There is a documented association between the vaccines and myocarditis, especially in young males. To date, a sparsity of evidence exists regarding associations of arrhythmias with the SARS-CoV-2 vaccines We present the case of a 42 year old lady, who was transferred to our hospital, following an out of hospital cardiac arrest. This was on the background of a recent discharge from her local hospital, after an anaphylactic reaction to the Pfizer/BioNTech Covid-19 vaccine. She suffered a cardiac arrest and received bystander cardiopulmonary resuscitation, with two shocks delivered by an automated defibrillator (AED) at the scene. Rhythm strips obtained from the AED, demonstrated polymorphic ventricular tachycardia. Cardiac Investigations including Echocardiography and CT Coronary Angiography were unremarkable. During her admission, she developed persistent episodes of non-sustained ventricular tachycardia, with R-on-T phenomenon. ( Figure 1 ) She was transferred to a tertiary cardiology centre for electrophysiology studies. An ajmaline test was negative, although ventricular ectopics were noted. There were no ectopics elicited during electrophysiology studies. There was a suggestion of a subtle J wave on a number of her ECGs and intermittent short PR interval ( figure 2 ), which would imply an early repolarisation syndrome such as J wave syndrome. Of note, during her stay in the coronary care unit, she developed intermittent tongue swelling and generalised ?urticarial rash which required treatment with steroids and antihistamines. She was transferred to a specialist centre, for further diagnostics including cardiac magnetic resonance imaging, electrophysiology studies and genetic screening for long QT syndrome. These investigations were all unremarkable, including a negative ajmaline test. A single chamber transvenous implantable cardiac defibrillator was inserted and she was discharged with beta-blockade. Discussion: Polymorphic ventricular tachycardia, has a multitude of causative factors including QT prolonging drugs, cardiac ischaemia, underlying genetic arrhythmias such as and catecholaminergic polymorphic ventricular tachycardia (CPVT) and inherited sodium and potassium channel mutations, most notably, long QT syndromes and Brugada syndrome. It can also be as a result of early repolarisation syndromes such as J wave syndrome. Myocarditis has now been linked to the covid vaccine, with a generally benign course of illness observed. It is unclear in our case, whether an underlying genetic predisposition, in combination with the covid vaccine and medications which can cause prolonged QT intervals, provoked this episode of polymorphic ventricular tachycardia. This patient, had never observed cardiac symptoms including chest pain or palpitations, leading a very active lifestyle prior to this event. We suspect an underlying early repolarisation syndrome, as a potential precipitant of this cardiac arrest. There has been an estimated rate of 11.1 cases of anaphylaxis, per 1 million Pfizer-BioNTech Covid-19 vaccines. Cardiovascular compromise, due to anaphylaxis, is well described in the acute setting. This patient had symptoms of a prolonged allergic reaction to the vaccine, as noted by her continued allergic symptoms days after her initial anaphylaxis. This may have contributed to the development of cardiovascular collapse in this case.